PENGARUH VOLUME PERDAGANGAN SAHAM, HARGA SAHAM DAN PENGEMBALIAN ABNORMAL TERHADAP KEPUTUSAN STOCK SPLIT - Fadiela Rokhiliantien Nufus; Nurma Gupita Dewi (JURNAL CAFETARIA, 2023)
The purpose of this study was to determine the effect of stock trading volume, stock prices and abnormal returns on stock split decisions. This study used purposive sampling and obtained 40 manufacturing companies in the consumer goods industry sector that were listed on the IDX for the 2019-2021 period. Methods of data collection using the method of documentation. The data analysis technique uses logistic regression analysis using the SPSS version 25 application. The results of this study indicate that stock trading volume has an insignificant negative effect on stock split decisions, stock prices have an insignificant positive effect on stock split decisions, and abnormal returns have a significant negative effect on stock split decisions. stock splits.